Deradicalizing student unrest in South Africa using decolonial approach - Bunmi Isaiah Omodan (Perspectives in Education)
South Africa has seen a surge in student protests, with virtually every institution of higher education experiencing some degree of disrupted productivity. This paper is a theoretical argument that presents the proponents of decoloniality as a tool to deradicalise students’ minds against radical student unrest in the university system and answers the question of how to deradicalise student unrest using decoloniality as a tool. The study is located with a transformative worldview, and the argument was analysed using conceptual analysis to make sense of the argument. The study is structured to explain what decoloniality is in relation to decoloniality of the minds, the assumptions, and its correlational evidence with the deradicalisation of student unrest. The findings revealed that disrupting colonial ideologies, knowledge reclamation, changing discourse structures, and decolonising practices are dimensions needed to decolonise student mindset towards deradicalisation of student unrest. The study concludes that these dimensions are the potential for peace and tranquility in the university system.